The breakers [large type] - Muller, Marcia (Muller, Marcia. Sharon McCone mysteries., 2018)
"On a foggy summer morning, private investigator Sharon McCone receives a call from her former neighbors, the Curleys. Their usually dependable daughter Chelle hasn't been answering their calls for weeks. Would Sharon check on her? Sharon arranges to visit the building Chelle had been living in and rehabbing in southwest San Francisco. Once it was a nightclub and bar, she learns, and a favorite destination for the city's elite during Prohibition. But there's something sinister about the space, and Sharon quickly discovers why. Lurking behind a divider screen is a ghastly art gallery: portraits and caricatures of mass murderers, long ago and recent. Jack the Ripper. The Zodiac and Zebra killers of the 1970s. Charles Manson and his girls. Scott Peterson, who killed his pregnant wife, Laci, and dumped her body into the Bay on Christmas Eve. What, an alarmed Sharon wonders, was Chelle doing in this chamber of horrors? And where is she now?"--